Family formation and post-secondary educational attainment among community college and 4-year college students: a longitudinal study - Rosenbaum, Janet E. (Frontiers in Education, 2025)
BackgroundEarly adulthood is a turning-point for educational attainment and family formation. Our understanding of whether family formation predicts educational attainment is incomplete for two growing populations: unmarried families and community college students. This study examined whether family formation among college students ages 18–24 predicts educational attainment at ages 25–32.MethodsWe test our hypothesis using data from the National Longitudinal Study of Adolescent and Adult Health attending community college (n = 1,530) and 4-year college (n = 2,897) in 2001 with graduation outcomes measured in 2008: certificate or above, associate’s degree or above, and bachelor’s degree or above. We estimated adjusted relative risks of each level of educational attainment using multivariate Poisson regression with robust standard errors controlling for pre-college grade-point average, test scores, college expectancies, demographics, socioeconomic status, and health risk behaviors.ResultsFour-year college students with children were 23% less likely to have earned a BA 7 years later than students without children [adjusted relative risk (ARR) = 0.77, 95% confidence interval (CI) (0.68, 0.89)], but community college students with children did not differ from students without children in attainment of certificate or above, associates or above, or bachelors or above [ARR = 0.93 (0.77, 1.13); 0.85 (0.67, 1.09); 0.61 (0.36, 1.04)]. Community and 4-year college students who were willing to leave college for marriage were, respectively, 71 and 21% less likely to have attained a bachelor’s or above than students who did not endorse leaving college for marriage [ARR = 0.29 (0.10, 0.83); 0.79 (0.67, 0.94)].ConclusionCommunity colleges may accommodate students with families better than 4-year colleges. Young adults who plan to start families during college may have higher educational attainment if they begin in community college. Colleges should reinforce persistence attitudes and provide material supports so that students do not perceive incompatibility between marriage and college completion.